AXL inhibition in treatment-resistant metastatic adenoid cystic carcinoma - Sivakamavalli Jeyachandran (Oral Oncology Reports)
Adenoid cystic carcinoma (ACC) presents a formidable challenge due to its slow growth, late-stage metastasis, and resistance to conventional therapies. Targeting the AXL receptor, implicated in aggressive tumor behavior and therapeutic resistance, offers a promising therapeutic avenue. Several studies demonstrate that AXL inhibition suppresses tumor cell proliferation, migration, and invasion, sensitizing ACC cells to chemotherapy and radiation therapy. Furthermore, AXL-targeted therapies modulate the tumor microenvironment, disrupting pro-tumorigenic signals. Despite challenges in clinical translation and tumor heterogeneity, early clinical findings show promise, suggesting AXL inhibition as a potential strategy to halt ACC progression and improve patient outcomes. The pursuit of precision-based treatments tailored to individual molecular profiles signifies a paradigm shift in ACC therapeutics, offering renewed hope for patients facing this relentless disease. Continued research into AXL biology and therapeutic strategies holds the potential to reshape the treatment landscape for metastatic, refractory ACC.